English for Business Studies. A course for Business Studies and Economics students: Student's Book - MacKenzie I. Ian (Cambridge Professional English)
English for Business Studies is a course for upper-intermediate and advanced level students who need to understand and talk about the key concepts in business and economics. The Third Edition of this best-selling business English course has been thoroughly revised to meet the needs of today's students. Covering the most important areas of management, production, marketing, finance and macroeconomics, it helps students to understand and talk about a wide range of business topics. Reflecting recent changes in the world's business and economic environment, the course now covers subjects like wikinomics, viral marketing, hedge funds, the subprime crisis and energy policy.